Association between Mean Platelet Volume (MPV) and Mayor Cardiovascular Incidence among Inpatient Acute Myocardial Infraction with ST-Elevation - Blessdova Fransza A.S.Hutabarat; Harris Hasan; Nizam Zikri Akbar (CV. Inara, 2022)
MPV value is an index of platelet associated with platelet activity. A larger platelet size shows a hyper-reactive platelet and accelerates thrombus formation with coronary circulation, leading to major cardiovascular events. Hence, this study was designed to investigate the relationship between MPV value and each type of major cardiovascular event in General Hospital Haji Adam Malik. This study was observational research with a cross-sectional design in General Hospital Haji Adam Malik in October 2014-January 2015 among sixty-nine ACS inpatients with ST-Elevation. The evaluated major cardiovascular events were death, heart failure, arrhythmia, and cardiogenic shock. The average MPV value of ACS patients with heart failure, cardiogenic shock, arrhythmia, death, and all major cardiovascular events was 10.08 fL, 10.40 fL, 10.00 fL, 9.76 fL, and 10.00 fL, respectively. Either major cardiovascular event did not show any significant difference in the average MPV value due to these P-Values > 0.05. Hence, it can be concluded that the MPV value cannot be used to predict the incidence of either major cardiovascular event in ACS patients.